Temperature Field Analysis of Laser Hardening of 18CrNi8 Gear based on ANSYS - Hui Yinglong; Wang Yuling; Yao Cuicui (Jixie chuandong)
An ANSYS finite element analysis of temperature field is carried out aiming at laser quenching process of a large modulus gear used in the overloading car,which involve the establishment of 3D model,load method,command flow of moving heat source,longitudinal section temperature distribution,determination of the hardening layer depth.According to ANSYS Post-processing methods,the case of heat flow in the processing,the temperature variation of typical nodes along the scanning line of the heat source and the depth direction as well as the cause and the solution of the widely different temperature between the surface before and after the laser speckle（which is caused momentarily "heat flux accumulation effect"）are analyzed.The analysis results show that laser quenching on the gear tooth surface can achieve good effect,which is validated by the experiment.